New spiro-indeno[1,2-b]quinoxalines clubbed with benzimidazole scaffold as CDK2 inhibitors for halting non-small cell lung cancer; stereoselective synthesis, molecular dynamics and structural insights - Assem Barakat; Saeed Alshahrani; Abdullah Mohammed Al-Majid; Abdullah Saleh Alamary; Matti Haukka; Marwa M. Abu-Serie; Luis R. Domingo; Sajda Ashraf; Zaheer Ul-Haq; Mohamed S. Nafie; Mohamed Teleb (Taylor & Francis Group, 2023)
Despite the crucial role of CDK2 in tumorigenesis, few inhibitors reached clinical trials for managing lung cancer, the leading cause of cancer death. Herein, we report combinatorial stereoselective synthesis of rationally designed spiroindeno[1,2-b]quinoxaline-based CDK2 inhibitors for NSCLC therapy. The design relied on merging pharmacophoric motifs and biomimetic scaffold hopping into this privileged skeleton via cost‐effective one-pot multicomponent [3 + 2] cycloaddition reaction. Absolute configuration was assigned by single crystal x-ray diffraction analysis and reaction mechanism was studied by Molecular Electron Density Theory. Initial MTT screening of the series against A549 cells and normal lung fibroblasts Wi-38 elected 6b as the study hit regarding potency (IC50 = 54 nM) and safety (SI = 6.64). In vitro CDK2 inhibition assay revealed that 6b (IC50 = 177 nM) was comparable to roscovitine (IC50 = 141 nM). Docking and molecular dynamic simulations suggested that 6b was stabilised into CDK2 cavity by hydrophobic interactions with key aminoacids.